NMDAR Encephalitis Associated With Acute Chikungunya Virus Infection: A New Trigger? - Nóbrega, Paulo Ribeiro; Morais, Norma Martins de Menezes; Braga-Neto, Pedro; Barros, Liziana Sofia da Silva; Honório, Fernanda Paiva Pereira; Dellavance, Alessandra; Hoftberger, Romana; Dutra, Lívia Almeida (Frontiers in Pediatrics, 2020)
Background: Anti-NMDAR encephalitis is the most frequent causes of autoimmune encephalitis. Chikungunya (CHIK) is an arbovirus responsible for outbreaks of fever, cutaneous rash and arthritis in underdeveloped countries, and a trigger for autoimmunity. Case Presentation: We report a five-year-old male patient with fever, myalgia, headache and conjunctivitis for 5 days. After one week he developed tonic-clonic seizures and evolved with dystonia and oromandibular dyskinesia followed by onset of focal motor seizures, decreased level of consciousness, dysautonomia and central apnea. Brain MRI was normal, CSF analysis revealed 15 cells, protein 16.6 mg/dL and glucose 68 mg/dL. Anti-NMDAR antibodies were detected in serum and CSF after three weeks of symptom onset. CHIK serology was positive for both IgM and IgG, suggesting a recent infection. Dengue and Zika serologies were negative. CSF PCR for herpes viruses and arboviruses (CHIK, Dengue and Zika) were negative. Conclusion: We report the occurrence of anti-NMDAR encephalitis after acute CHIK infection. The biphasic course, positivity for both CHIK IgM and IgG and negative CHIK CSF PCR results, as well as a dramatic response to immunotherapy suggest an immune-mediated pathogenesis. Because of the global epidemic of CHIK infection and unknown mechanisms involving CHIK and autoimmunity, patients with acute CHIK infections and neurological manifestations should be considered for antineuronal antibody testing.